Provide a structural model for predicting distress tolerance based on dark personality traits and perceived social support mediated by defense styles in divorce-seeking clients - Akhgary, Zahra; Ebrahimi Moghadam, Hossein; Davari, Rahim (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the presentation of a structural model for predicting distress tolerance based on dark personality traits and perceived social support mediated by defense styles in divorce-seeking clients. Method: The research method was analytical-correlation by structural equation modeling. The statistical population of the present study was the clients seeking divorce in family counseling clinics in Tehran in 2021. The sample size of 260 people was selected by available sampling method and used by Simmons and Gahr (2005) Distress Tolerance Scale, Johnson & Webster's Dark Triangle (2010), Zimet et al.'s Multidimensional Perceived Social Support Scale (1988) and Defense Mechanism Questionnaire. Andrews et al. (1993) responded. The proposed model was then analyzed by structural equation modeling using SPSS and AMOS version 24. Results: The results showed that direct paths of personality traits and defensive styles were significant on distress tolerance (P